Effects of different rehabilitation modality on cardiopulmonary function in patients with acute coronary syndrome after revascularization - Chen, Wanping; Feng, Yan; Yu, Meili; Zhang, Zhaoguo; Wu, Jiahui; Liu, Wenxian; Gu, Wei (Frontiers in Cardiovascular Medicine, 2024)
Objective To investigate the effects of different rehabilitation modalities on cardiopulmonary function in patients with acute coronary syndrome after revascularization. Methods Two randomized controlled trials were conducted. All patients were stable for more than 48 h and less than 1 week after revascularization for acute coronary syndrome and were randomly assigned to Group A (home-based rehabilitation group) or Group B (center guided home-based rehabilitation group). The cardiopulmonary exercise test was mainly performed before and 3 months after cardiac rehabilitation (at the end of intervention). The primary endpoints of the study were peak oxygen uptake (VO2peak), and the secondary endpoints were maximum metabolic equivalents (METs), anaerobic threshold exercise load (Load AT), maximal workload (Load max), and anaerobic threshold oxygen uptake (VO2 AT). Results A total of 106 patients were included in the study, with 47 patients in Group A (with 6 losses) and 50 patients in Group B (with 3 losses). There were no significant difference between the two groups in terms of age, gender, body mass index (BMI), left ventricular ejection fraction(LVEF), low-density lipoprotein cholesterol(LDL-C),cardiovascular risk factors. In Group A, no significant differences in CPET indices were observed before and after the intervention. In Group B, values of maximum metabolic equivalents (METs), peak heart rate (PHR), anaerobic threshold exercise load (Load AT), maximal workload (Load max), maximum ventilation per minute (VE max), peak oxygen uptake (VO2peak), anaerobic threshold oxygen uptake (VO2 AT) and maximum oxygen pulse (VO2/HRmax) were higher than those before the intervention (P < 0.05). In addition, METs (max), Load AT, Load max, VO2 AT, and VO2peak in Group B were higher than those in group A (P < 0.05). The change rates of VO2peak, METs(max), PHR, Load max, VO2 AT, VE max, VO2/HR(max) in the two groups were significantly different before and after intervention (P < 0.05). Conclusion Cardiac exercise rehabilitation is helpful for improving patients’ cardiopulmonary endurance and quality of life. Moreover, rehabilitation modalities with regular hospital guidance can improve cardiopulmonary function in a shorter period,which seems to be more effective than a complete home-based rehabilitation model. Clinical Trial Registration http://www.chictr.org.cn, identifier (ChiCTR2400081034).